ARTISTIC CHRONOTOP IN VALERIY SHEVCHUK’S FAIRY TALES - Dybovska, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of chronotope of literary texts. The concepts of «chronotope» are determined. Differentiation and classification of concepts «space» and «time» in literary texts are reviewed. Temporal space on the base of Valeriy Shevchuk’s «The lady of flowers» is analyzed.